Answer:
z=3
Step-by-step explanation:
2(2z -4)=4
Divide by 2
2/2(2z -4)=4/2
2z-4 = 2
Add 4 to each side
2z-4+4 = 2+4
2z = 6
Divide by 2
2z/2 = 6/2
z=3
Answer:
y= -76
Step-by-step explanation:
y/4=-19
*4 *4
Answer:
417.084
Step-by-step explanation:
9*6.5+12*9.757+14*17.25
58.5+117.084+241.5
⇒417.084
Answer:
201
Step-by-step explanation:
3.14*8*8=201
Answer:
KJFJDSKLJDKLFJDSKJDSFKDMF;DS MDF NM FDSF DS FSDFSD FJJKFSDN DSF DSJFJDSFDNFDFNDMFDNSAFJASNF,MASFNAS2`1849 ,MNFNMADBFASBJ2L31U93O2KQN 4Y72 7IW4N LOOK THIS UP TO GET ANSWERS
Step-by-step explanation: